Spatial distribution of lichen communities and air pollution mapping in a tropical city: Medellín, Colombia - Correa-Ochoa, Mauricio Andres (2021)
Introduction: Enough scientific evidence is available on the harmful effects of air pollution on the health of human beings, fauna, flora, and ecosystems in general. The mechanical and electronical monitoring networks are the first option for the air quality diagnosis, but they do not allow a direct and precise assessment of the impacts in living organisms that may result from the exposure to air pollutants. Objective: To evaluate the changes in the composition of corticulous lichen communities as a response to various stress factors in areas with different levels of air quality to diagnose the state of pollution or intervention in an area with a more complete option. Methods: Air quality contrasts and changes in richness and coverage of corticulous lichens in response to different stress factors, such as land use and distance to roads, in three different biomonitoring areas, were evaluate using GIS, and the data are presented in an easy-to-understand grey scale coded isoline map. Results: Indicators such as lichen coverage (R= -0.4) and richness (R= -0.7) are inverse correlated with PM2.5 concentrations in each area. A total of 110 lichen species were identified, being Phaeophyscia chloantha (Ach.) Moberg and Physcia poncinsii Hue the most frequent species (present in 38 and 33 % of the 86 sampled phorophytes, respectively). The intra-area relationships of lichen richness exhibit significant relationships with regards to the land use and distance to roads (with correlations coefficients greater than 0.5) and the Simpson index was higher than 0.9, in places with better conditions in terms of air quality and microenvironments, likewise the resistance factors calculated suggest that the most sensitive species can be found in environments with a lesser degree of disturbance. Conclusion: These evaluations represent more criteria elements for the diagnosis of the environmental health in the biomonitoring areas.